2020
DOI: 10.1038/s41598-020-64412-7
|View full text |Cite
|
Sign up to set email alerts
|

First report of AChE1 (G119S) mutation and multiple resistance mechanisms in Anopheles gambiae s.s. in Nigeria

Abstract: First report of AChE1 (G119S) mutation and multiple resistance mechanisms in Anopheles gambiae s.s. in nigeria ifeoluwa Kayode fagbohun 1 ✉ , emmanuel taiwo idowu 1 , olubunmi Adetoro otubanjo 1 & taiwo Samson Awolola 2 Susceptibility and PBO synergist bioassays were done using 3-5 days old female Anopheles mosquito collected from Lagos State, Nigeria with WHO test papers DDT (4%), permethrin (0.75%), Bendiocarb (1%) and PBO (4%) according to standard procedures. The activities of cytochrome P450s, glutathione… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 50 publications
(63 reference statements)
2
7
1
Order By: Relevance
“…gambiae s.s. tested. This was contrary previous findings in Nigeria [26,28,29,31,33,37] where the L1014F mutation was found in mosquito populations. The result of the study also contrast others from several parts of West and Central Africa where L1014F mutation were observed [29,[38][39][40] .…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…gambiae s.s. tested. This was contrary previous findings in Nigeria [26,28,29,31,33,37] where the L1014F mutation was found in mosquito populations. The result of the study also contrast others from several parts of West and Central Africa where L1014F mutation were observed [29,[38][39][40] .…”
Section: Discussioncontrasting
confidence: 99%
“…gambiae s.s. tested from all the site were positive for G119S mutation. This is in agreement with recent results in Nigeria [33,42] where G119S mutation genes were detected. The Ace-1 R mutation has been linked to carbamates and organophosphate cross resistance in malaria vectors.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Suspected resistance was recorded in An. gambiae to bendiocarb in this study, previous studies have reported similar results in malaria vector in the Southwest and Northern Nigeria 27 , 30 , 32 though susceptibility was recorded in southeast Nigeria 28 . Carbamates are important in malaria vector control especially for IRS to reduce selection pressure on pyrethroid, the emergence of resistance to this class of insecticide may have a deleterious effect on the control of malaria in the study area.…”
Section: Discussionsupporting
confidence: 87%
“…The rapid emergence and spread in insecticidal resistance among the malaria vector population to WHO-approved insecticides presents a challenge to the control of malaria in sub-Saharan Africa 12 , 13 . In Nigeria, insecticides resistance to different classes of insecticides in malaria vectors has been reported in various parts of the country 14 – 16 , the presence of metabolic and knockdown resistance mechanisms has also been reported 17 19 .…”
Section: Introductionmentioning
confidence: 99%